Pembekalan Moderasi Beragama Generasi Muda Di BLKK Ponpes Qur’any Bulurejo Jombang - Ali Mustofa; Nurul Indana; Arif Rahman Hakim (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
The purpose of this community service activity is to equip young people who take part in training at BLKK Qur'any with additional content, namely religious moderation. This community service uses the Participatory Action Research approach or commonly abbreviated as PAR. The stages of implementing the service, namely preparation, implementation, and evaluation. The results of the service showed that a more comprehensive understanding was obtained in BLKK students about religious moderation provided through lectures, and learning media. The results of training and debriefing on religious moderation are generally quite significant and show a positive relationship, but more towards a humanist attitude. However, it is this humanist attitude that can lead them to be tolerant and moderate. With the attitude of religious tolerance religious tolerance in children, it will prepare children as the next generation of the nation to have an attitude of mutual respect, respect for differences, and live the freedom of rights in choosing each other's beliefs. choose each other's beliefs.